Manage the talent of university actors through leadership and interest: Researchers and management positions - López-Hernández, Rosa Eva; Vázquez-Reyes, Estrella (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Talent management in higher education is key to quality education. This study aimed to understand and describe the categories that support the potentialization of the talent of researchers and to know the motivating interests of leadership development. It was conducted under the qualitative approach. We found that talent management is hindered by inefficient practices in recruitment, personnel selection, as well as the weighting of monetary incentives in researchers for their performance. It is recommended to address succession-planning studies in educational organizations to ensure the reserves of key talent.